Once upon a snowstorm - Johnson, Richard, 1976- (London : Faber & Faber, 2018)
After a boy becomes separated from his father during a snow storm, he finds himself lost in the woods, but when he befriends some woodland animals, they help him out.
"A Faber picture book."
Keywords: Snow -- Fiction; Fathers and sons -- Fiction; Forest animals -- Fiction; Missing persons -- Fiction; Human-animal relationships -- Fiction; Stories without words; Snow -- Fiction; Father-son relationship -- Fiction; Forest animals -- Fiction; Missing persons -- Fiction; Human-animal relationships -- Fiction; Stories without words